Dental treatment on a German warship during a three-month deployment. Issue 1 (17th July 2013) - von Wilmowsky, Cornelius; Kiesewetter, M R; Moest, T
Abstract : Introduction: Despite routine dental screenings and treatments before military deployments, dental emergencies may arise due to acute infections, trauma or failed restorations. The purpose of this study is to evaluate the dental service during a three-month deployment on a German warship. Methods: A retrospective analysis of dental attendances and treatments in a German naval task group of three ships with an average total of 650 soldiers. Diagnosis, treatments performed, percentage of emergencies, routine procedures and numbers of appointments were recorded. Results: Out of 650 soldiers, there were 71 patients (10.92%) with a mean age of 25.1±5.3 years. Out of 136 treatments, 17.65% were for emergency treatment, which is equivalent to 3.69% of all servicemen of the task group. Combining the reasons for dental emergencies, 95.84% were caused by caries. Conclusions: The pre-screening of sailors before an overseas deployment is necessary to avoid severe dental treatments. Caries remains the main cause for dental emergencies, and medical doctors should be trained to treat caries lesions if a dentist is not on board.